FLORA DAS FLORESTAS ESTACIONAIS SEMIDECIDUAIS DO ESTADO DE MATO GROSSO DO SUL - MOYSES, Debora Gomes,; BUENO, Marcelo Leandro,; FARIAS, Ivan Justino,; VIEIRA, Eliane,; PONTARA, Vanessa, (ANAIS DO ENIC, 2024)
-